Learning Tool Project to Create PBL Model to Stimulate Computational Thinking Ability of Students - Tia Yolanda Lubis; Bornok Sinaga; Mulyono Mulyono (Randwick International of Education and Linguistics Science Journal, 2023)
The aim of this research is to analyze the validity of learning tools developed by applying the PBL model to improve students' computational thinking skills at SMP Negeri 37 Medan and to analyze the effectiveness of learning tools developed by applying the PBL model to improve students' computational thinking skills at SMP Negeri 37 Medan. This research uses research and development (R&D) methods. The results show that in trial I, the posttest results of students' computational thinking abilities were obtained, namely, 11 students (36.7%) got the poor category, 11 students (36.7%) got the sufficient category, 8 students (26%) got the good category. .6%), and no students obtained the very good category. In trial II, there were no students who got the poor category (0%), 8 students got the sufficient category (26.7%), 8 students got the good category (26.7%), and there were 8 students who got the good category (26.7%). 26.7%), who received the very good category were 14 students (46.6%). So, it could be concluded that the learning tools developed by applying the PBL model to improve students' computational thinking skills at SMP Negeri 37 Medan are valid. Learning tools developed by applying the PBL model to improve students' computational thinking skills at SMP Negeri 37 Medan are practical.